“De pé para a bandeira e de joelhos para a cruz" : nacionalismo cristão na política externa dos governos Bolsonaro e Orbán - Henrique Gomes e Silva (2024)
The present work aims to observe the presence of Christian nationalism in the foreign policy of right-wing populist governments, through comparative case studies between the government of Jair Bolsonaro in Brazil and Viktor Orbán in Hungary. Right-wing populism is a phenomenon characterized by charismatic leaders who claim to represent the general will of the nation by defending the pure people against the corrupt elite, with distinctly nativist and authoritarian traits. Christian nationalism is an ideology present in many of these regimes, advocating the idea that the nation-state is inherently Christian and should prioritize initiatives guided by a conservative view of Christianity in its programmatic agenda. Additionally, this ideology uses the religious component as a criterion to define who is part of the people in populist discourse. Role Theory is used to explain how leaders define the roles of their states on the international stage, establishing principles, objectives, and common actions, which also facilitates ideological and strategic approximation between nationalist governments. To investigate the presence of Christian nationalism in foreign policy speeches, discourse analysis was chosen as the method. The case studies examine the main populist characteristics of each government, the political use of religion, and conclude with an analysis of the collected speeches. It is concluded that both Bolsonaro and Orbán attribute the identity of a Christian nation to their respective countries, and that the role Brazil and Hungary are to play on the international stage is aligned with this identity. This includes the anti-abortion fight, the defense of religious freedom, and the protection of persecuted Christians. Moreover, it involves the choice of common enemies, such as globalism, the left, the LGBTQI+ movement, and Islamic peoples, as well as the establishment of shared partnerships with countries like the United States, Israel, and Poland, forming an international populist alliance.